Preliminary crystallographic studies of citrate synthase from an Antarctic psychrotolerant bacterium - Gerike, U; Russell, RJM; Danson, MJ; Russell, N; Hough, DW; Taylor, Garry Lindsay (1998)
Recombinant citrate synthase from a psychrotolerant bacterium, DS2-3R, recently isolated in Antarctica, has been crystallized. The crystals belong to space group P6(1)22 or P6(5)22, with cell dimensions a = b = 70.8, c = 307.8 Angstrom. Diffraction data collected on a synchrotron from a cryoprotected crystal extend to at least 2.0 Angstrom. Knowledge of the structure of this enzyme Rill add to the understanding of told activity and thermolability and will be of biotechnological interest. Previously, the structure of citrate synthase from Archaea inhabiting environments at 328 and 373 K, has been reported. This present study will extend our understanding of the structural integrity and activity of proteins at the temperature extremes of life.